Kaji Eksperimental Variasi Jarak Turbin Angin Venturi Dengan Turbin Angin Propeler Terhadap Performa Hybrid Wind Turbine - Eldhy Susetio; Iwan Kurniawan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The hybrid wind turbine in this study is a horizontal axis wind turbine, whichcombining of two different wind turbines.A turbine propeller shaft is 2 m in diameter with blade profiles of S833 and ball wind energy (venturi turbine) of 0.5 meters by the number blade of 5 pieces. Venturi turbine is placed in front of the propeller turbine. This study varying the distance between the rear hub of Venturi turbine by propeller turbine hub is 5 cm, 10 cm and 15 cm. Testing begins with collecting data on the turbine propeller, then performed the retrieval of data from the merger of Venturi turbine with turbine propeller hub by varying the distance between the two turbines. This study suggests that the addition of Venturi wind turbine in front of the propeller wind turbine produces round and a higher power than the wind turbine propellers without Venturi wind turbine in front of it. The addition of the power generated in the generator's turbine hybrid that a distance of 5 cm power generators will increase the amount of 12.7%, while at a distance of 10 cm power generator increases the amount of 28.5%, and the last on the addition of 15 cm distance power generators increased 34.3% magnitude. Keywords: Hybrid wind turbine, Venturi turbine, turbine propeller